Simultaneous inactivation of antibiotic-resistant bacteria and degradation of antibiotic-resistant genes in alkalised human urine - Demissie, Natnael; Nordin, Annika; Simha, Prithvi; Conroy, Isis; Sun, He; Schnürer, Anna; Vinnerås, Björn; Desta, Adey (Frontiers in Microbiology, 2025)
The coexistence of pharmaceuticals and microorganisms in source separated urine poses a risk for the development of antimicrobial resistance (AMR), especially when urine-based fertilizers are applied to soils. While prior studies have investigated pathogen inactivation in source-separated wastewater matrices, few have evaluated the simultaneous fate of antibiotic-resistant bacteria (ARBs) and their corresponding resistance genes (ARGs) in real urine matrices, particularly under alkaline conditions. Here, we studied the inactivation of β-lactamase-producing Escherichia coli and vancomycin-resistant Enterococcus faecium and the degradation of their respective ARGs (blaCTX − M and van-A) in alkalized, unhydrolyzed urine (pH 10.8 and 12.5) treated with UV (65 W low pressure dichromatic mercury lamp at 185/254 nm), hydrogen peroxide (1.25 g L−1 H2O2), and their combination (UV/H2O2). UV/H2O2 treatment resulted in >7 log10 inactivation of both ARBs, with inactivation rate constants of −0.058 log10 cfu min−1 (E. coli, UV) and −0.093 log10 cfu min−1 (E. faecium, UV/H2O2). In contrast, ARG reduction was limited with UV alone and negligible with H2O2 alone. Gene copy reductions of 3 log10 (blaCTX − M, k = −0.055 log10 copies min−1) and 2 log10 (van-A, k = −0.040 log10 copies min−1) were observed under UV/H2O2. Notably, brief storage (>3 h) at pH 12.5 achieved similar ARB inactivation and ARG reduction as 80 min of UV/H2O2 treatment at pH 10.8, offering a low-energy alternative for sanitizing source-separated urine.